Refining a pedagogical approach for employing design thinking as a catalyst - Raghavendra Reddy, Guder; McDonagh, Deana; Harris, Maurita; Rogers, Wendy A. (Design and Technology Education: An International Journal, 2021)
There is an increasing interest in design and creative thinking processes in the Sciences, Technology, Engineering, and Mathematics (STEM) and health education disciplines. Many new degree programs are integrating design thinking into their syllabi, with the intention of bringing creative problem-solving methods to these disciplines. In reality, the exposure these students get is minimal, and it does not provide enough foundation for them to use the knowledge and apply the process(es) in real-life situations. There is an increased awareness of the importance of design thinking in the innovative process. More and more STEM, business, and health establishments are embedding trained designers into their research teams – yet many designers are not equipped to work on interdisciplinary teams. Design students tend to approach problems more intuitively, opportunistically, and build on creative leaps of imagination whereas, STEM and health disciplines are often more algorithmic, systematic, and rationale. This can often generate tension in interdisciplinary teams, especially when traditional disciplines (e.g., Engineering, Sciences) are integrating relatively newer thinking (e.g., design thinking).In this paper, we share the outcome of a phenomenological study on a high-functioning interdisciplinary team working on a health innovation project focused on aging with a disability. This case study illustrates the skill set needed for designers, health and technology professionals to make a significant contribution to its overall outcome. We identified key attributes that contribute towards being an effective member of interdisciplinary teams. Based on this study, we propose a pedagogical approach to better equip design, STEM, and Health students to be more competitive in changing economic expectations and ensure more impactful design outcomes.